Interregional Transfers for Pandemic Surges. (10th October 2020) - Michelson, Kenneth A; Rees, Chris A; Sarathy, Jayshree; VonAchen, Paige; Wornow, Michael; Monuteaux, Michael C; Neuman, Mark I
Abstract: Background: Hospital inpatient and intensive care unit (ICU) bed shortfalls may arise due to regional surges in volume. We sought to determine how interregional transfers could alleviate bed shortfalls during a pandemic. Methods: We used estimates of past and projected inpatient and ICU cases of coronavirus disease 2019 (COVID-19) from 4 February 2020 to 1 October 2020. For regions with bed shortfalls (where the number of patients exceeded bed capacity), transfers to the nearest region with unused beds were simulated using an algorithm that minimized total interregional transfer distances across the United States. Model scenarios used a range of predicted COVID-19 volumes (lower, mean, and upper bounds) and non–COVID-19 volumes (20%, 50%, or 80% of baseline hospital volumes). Scenarios were created for each day of data, and worst-case scenarios were created treating all regions' peak volumes as simultaneous. Mean per-patient transfer distances were calculated by scenario. Results: For the worst-case scenarios, national bed shortfalls ranged from 669 to 58 562 inpatient beds and 3208 to 31 190 ICU beds, depending on model volume parameters. Mean transfer distances to alleviate daily bed shortfalls ranged from 23 to 352 miles for inpatient and 28 to 423 miles for ICU patients, depending on volume. Under all worst-case scenarios except the highest-volume ICU scenario, interregional transfers could fully resolve bed shortfalls. To do so, mean transfer distances would be 24 to 405 miles for inpatients and 73 to 476 miles for ICU patients. Conclusions: Interregional transfers could mitigate regional bed shortfalls during pandemic hospital surges. Abstract : Based on simulations of hospitals with shortfalls or surpluses of hospital beds during a pandemic surge, interregional transfers could be trialed as a means of alleviating such surges.